PENGEMBANGAN e-LKPD BERBASIS KEARIFAN BUDAYA JAWA SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI KELAS V SDN 106830 SIDODADI RAMUNI - Sutriono; Tiflatul Husna; Khairiah; Juliandi Siregar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Basic education plays a strategic role in shaping character and enhancing students' cognitive abilities. However, the reality on the ground shows that learning is still dominated by conventional, less interactive methods, so students often experience difficulties in understanding the material. Furthermore, the minimal integration of local culture in learning causes students to become increasingly distant from the noble values of their region, including Javanese culture, which is rich in moral and social philosophy. This condition demands learning innovations that can connect material to the cultural context and students' daily lives. Based on observations at SDN 106830 Sidodadi Ramunia, as many as 85% of fifth-grade students are Javanese, yet learning still uses conventional, less engaging student worksheets (LKPD). As many as 70% of students stated that they were bored with the monotonous LKPD, and 65% had difficulty understanding the content because it was not contextual. On the other hand, technological developments provide a significant opportunity to create more engaging and interactive digital learning media, one of which is through the development of e-LKPD (Electronic Student Worksheets) based on local culture. The development of e-LKPD based on Javanese cultural wisdom is expected to be a solution to improve student motivation, understanding, and character. This media is designed with an attractive appearance, interactive features, and contains cultural values such as politeness, mutual cooperation, and gratitude. The integration of culture and technology in learning not only makes the learning process more meaningful and contextual but also plays a role in preserving local culture through education. Thus, e-LKPD based on Javanese cultural wisdom can be an effective innovation for creating relevant learning in the digital age.